Osteomalacia Induced by Renal Tubular Acidosis Type 1 - Steven Sutanto Sihombing; Anna Ariane; RM Suryo Anggoro Kusumo Wibowo; Bambang Setyohadi (Indonesian Rheumatology Association, 2017)
Renal Tubular Acidosis, a group of disorders characterized by defective renal acid-base regulation, can impair mineralization of bone matrix in adults known as osteomalacia. RTA is classified into 3 major forms, such as proximal RTA or type 2; distal RTA or type 1; and hyperkalemic RTA or type 4. Among all type of RTA, proximal RTA or type 2 is known have association with Fanconi syndrome and bone involvement. However, distal RTA or type 1 can also cause osteomalacia. Hereby we report a case of 22 years old Asian woman who wasfirstly diagnosed with distal type RTA several years ago then started developing bone involvement recently. She was complaining with low back pain due to fracture on left medial side of inferior pubic ramus and endplate fracture on right side superior L4 and BMD examination showed low mineral density. She was diagnosed with osteomalacia induced by distal type RTA due to the loss of calcium salts from bone and hypophosphatemia.Keywords: Osteomalacia; Renal Tubular Acidosis; Hypokalemia; Hypophosphatemia